Juridical Analysis of the Authenticity of Notary Deed after Apostille is Implemented in Indonesia - Unggul Basoeky (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
In the era of disruptive technology and the Covid-19 pandemic, civil transactions between communities have been dominated by using electronic means with internet devices. Communities across countries can easily interact and transact without time and space boundaries in a cyber/virtual world. Electronic commerce traffic (e-commerce) is the leading choice for the global community in meeting their needs and lifestyles. This research uses qualitative research with a descriptive analysis approach; this research method uses normative juridical research using a statutory proVcess, a conceptual approach, and a comparative approach. From this research, it can be seen that an apostille can be implemented on notary deeds while maintaining authenticity as an authentic deed that has perfect evidentiary quality. With the adoption and adoption of the Apostille method in Indonesia, the chain of formalities for the issuance of notary deeds needs to be redesigned and adjusted to the provisions of the apostille convention with a new approach and method in transforming the procedure for issuing notary deeds that are better and following the needs in the era of globalisation and electronics.